2020
DOI: 10.3390/jcm9124092
|View full text |Cite
|
Sign up to set email alerts
|

Energy Metabolism Disturbances in Cell Models of PARK2 CNV Carriers with ADHD

Abstract: The main goal of the present study was the identification of cellular phenotypes in attention-deficit-/hyperactivity disorder (ADHD) patient-derived cellular models from carriers of rare copy number variants (CNVs) in the PARK2 locus that have been previously associated with ADHD. Human-derived fibroblasts (HDF) were cultured and human-induced pluripotent stem cells (hiPSC) were reprogrammed and differentiated into dopaminergic neuronal cells (mDANs). A series of assays in baseline condition and in different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 52 publications
(63 reference statements)
3
11
0
Order By: Relevance
“…and our finding might also point to a role in ADHD. As NNMT plays a role in glucose and insulin metabolism our finding might be connected to the cooccurrence of ADHD and obesity on the one hand and our previous findings on impaired energy impairment in all the investigated PARK2 ADHD CNV cell types(Martins-Silva et al, 2021;Palladino et al, 2020).…”
supporting
confidence: 56%
See 3 more Smart Citations
“…and our finding might also point to a role in ADHD. As NNMT plays a role in glucose and insulin metabolism our finding might be connected to the cooccurrence of ADHD and obesity on the one hand and our previous findings on impaired energy impairment in all the investigated PARK2 ADHD CNV cell types(Martins-Silva et al, 2021;Palladino et al, 2020).…”
supporting
confidence: 56%
“…Duplication and deletions were investigated separately as well as grouped and compared to healthy and ADHD wild-type variant carriers. Grouped analysis aimed at increasing sample size, similar to our previous study where similar effects in the same direction have been found in as well deletion as duplication carriers (Palladino et al, 2020). In the following, the terms ADHD PARK2 deletion duplication carriers, wildtype ADHD and wildtype healthy control are used for our cell lines and their donors, adding the respective cell line numbers.…”
Section: Participants and Cell Linesmentioning
confidence: 94%
See 2 more Smart Citations
“…Palladino et al (2018) investigated a candidate gene for ADHD, PARK2, coding for a protein involved in mitochondria functioning, using human dermal fibroblasts and iPSC-derived dopaminergic neurons from patients suffering from ADHD. They found that carrying a copy number variation of PARK2 might impact mitochondrial dynamics and thereby processes important during developmental periods ( Palladino et al, 2020 ). Considering their results, they suggest substances affecting mitochondria function (antioxidants) as potential treatment options.…”
Section: Neuronal Models For Disorders Of the Brainmentioning
confidence: 99%